Prospective, randomized double blind comparative study of safety and efficacy of carvedilol versus atenolol in patients of mild to moderate hypertension - R., Swathi Ratnam; P., Usha Kiran; Rajasekhar, S. V. R.; Naidu, M. Prasad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Carvedilol is a new cardiovascular compound with the combined pharmacologic properties of nonselective ß-blockade and vasodilation. The Aim of the study was to compare the safety and antihypertensive efficacy of 25mg Carvedilol once daily with 50mg atenolol once daily in patients with mild to moderate essential hypertension. Methods: This was a single center study conducted in Rangaraya Medical College, Kakinada. 80 eligible patients with mild to moderate hypertension were randomized to receive 25mg Carvedilol once daily (40 patients) or 50mg atenolol (40 patients) in a double-blind 12-week treatment phase. At each visit 0, 4, 8 and 12 weeks of treatment, sitting Blood Pressure (BP) and heart rate were measured. The effect on BP reduction within the group is compared by paired “t”test and the effect on reduction of BP between two study groups compared by unpaired “t”test. Results: After 12 weeks of treatment, the mean reduction of SBP (Systolic Blood Pressure) with carvedilol is 22.33±8.31mmHg with no Significant difference (p >0.05) compared to atenolol group mean reduction in SBP of 21.37±10mm Hg. The mean reduction in DBP (Diastolic Blood Pressure) after completion of the study in carvedilol group is 6.75±4.82mm Hg with no Significant difference (p >0.05) compared to atenolol group mean reduction in DBP of 8.55±5.25mm Hg. No significant difference seen in the efficacy parameters of both the drugs. The incidence of adverse effects such as bradycardia, headache, nausea, vomiting, hypotension and rash is less with carvedilol. Conclusions: In patients with mild to moderate hypertension, there was no statistically significant difference between efficacy of carvedilol or atenolol with regard to the degree of reduction in BP or the percentage of patients achieving a response to therapy but carvedilol showed a better safety profile when compared to atenolol.